Method for processing and preparing hole transport layer of organic solar cell
By using sodium hydroxide aqueous solution treatment and annealing treatment in the nickel oxide hole transport layer, the interface defects between the nickel oxide and the perovskite layer and the ionic liquid arrangement problems are solved, and the performance and stability of solar cells are improved.
Patent Information
- Application Number
- CN202510142500.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-10
AI Technical Summary
In existing trans perovskite solar cells, there are interface defects and disordered ionic liquid arrangements between the nickel oxide hole transport layer and the perovskite absorbing layer, which affects device performance and stability.
The nickel oxide film is processed by using aqueous sodium hydroxide solution, adjusting its pH value and covering it on the hole transport layer, and annealing is performed to form an effective passivation layer to solve the interface problem.
The conductivity and carrier concentration of the nickel oxide film are improved, the energy band matching with the organic light absorbing layer is enhanced, the interfacial defect density is reduced, and the performance and stability of perovskite devices are improved.
Smart Images

Figure CN119604161A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to solar cells, and in particular to a method for processing and preparing a hole transport layer of an organic solar cell. Background Art
[0002] Solar energy is a green, clean energy source that is easily accessible. After years of development, the photoelectric conversion efficiency of perovskite solar cells has been greatly improved. Among them, inverse perovskite solar cells have received widespread attention due to their simpler and cheaper preparation process, low-temperature film formation, no obvious hysteresis effect, and suitability for combination with traditional solar cells to prepare stacked devices.
[0003] In inverse perovskite solar cells, commonly used hole transport layers include PEDOT:PSS (a polymer aqueous solution, mainly composed of PEDOT (polymer of 3,4-ethylenedioxythiophene monomer) and PSS (polystyrene sulfonate)), PTAA (poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine]) and NiO x Among them, PEDOT:PSS and PTAA are organic materials, NiO x As an inorganic material, the devices made of PEDOT:PSS have a low open circuit voltage due to the poor matching of the energy band with the perovskite light-absorbing layer and the existence of serious interface recombination. The devices made of PTAA have better performance, but the cost and synthesis cost of the material itself are high, large-area deposition is difficult, and there is a potential risk of decomposition in a humid and hot environment.
[0004] As a hole transport layer in inverse perovskite solar cell devices, NiO x It has many advantages. According to the energy level diagram of each carrier transport layer and perovskite absorption layer, the HOMO energy level of PTAA is -5.0eV, the HOMO energy level of PEDOT:PSS is -5.1eV, while the valence band energy level of MAPbI3 perovskite material is -5.49eV, and the reception energy level of FAPbI3 perovskite material is -5.50eV. The energy level mismatch between PTAA and PEDOT:PSS in hole transport is relatively serious. NiO x The valence band energy level is -5.4eV, which is close to the valence band energy level of MAPbI3 and FAPbI3 perovskite materials. The energy level mismatch problem is relatively small, which can bring higher open circuit voltage and efficiency.
[0005] In actual experiments, the inventors found that NiO prepared by DC magnetron sputtering xThere are still some problems that restrict the development of thin films. For example, after the preparation of traditional nickel oxide thin films, there will be defects at the contact interface between them and the perovskite light-absorbing layer. The ionic liquid is arranged disorderly at the interface between nickel oxide and the perovskite light-absorbing layer, and the passivation effect is poor, which in turn affects the performance and stability of perovskite devices. Summary of the invention
[0006] In order to solve the defects of the prior art, the present invention provides a method for processing and preparing a hole transport layer of an organic solar cell.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: The present invention provides a method for processing a hole transport layer of an organic solar cell, comprising the following steps: S1: preparing a nickel oxide hole transport layer film and washing the nickel oxide film with deionized water; S2: preparing a liquid to be adjusted and measuring an initial pH value of the liquid to be adjusted; S3: Calculate the required volume of sodium hydroxide aqueous solution, and add an appropriate amount of sodium hydroxide aqueous solution to the liquid to be adjusted in step S2 to adjust the pH of the solution to an appropriate range; S4: evenly spread the solution in step S3 on the surface of the cleaned nickel oxide hole transport layer film, and soak for 1-15 minutes to ensure sufficient reaction; S5: Rinse the nickel oxide hole transport layer film with deionized water to remove excess sodium hydroxide aqueous solution, and then dry the rinsed film to complete the post-processing.
[0008] As a preferred technical solution of the present invention, the pH value of the solution in step S3 is 9-10.
[0009] As a preferred technical solution of the present invention, the time for rinsing with deionized water in step S5 is 1-5 minutes; The washed film is placed in an oven for drying at a temperature of 40°C-70°C and a drying time of 10-30 minutes.
[0010] As a preferred technical solution of the present invention, both step S4 and step S5 are performed under air or inert gas.
[0011] As a preferred technical solution of the present invention, the following steps are also included: S6: soaking the post-treated nickel oxide film in a fluoride solution and performing fluorination treatment, soaking for 1-15 minutes to ensure sufficient reaction, and the concentration of the fluoride solution is 0.1-0.5 mol / L.
[0012] As a preferred technical solution of the present invention, the following steps are also included between step S1 and step S2: S11: directly coating the cleaned nickel oxide film with a fluoride solution, soaking for 1-15 minutes to ensure sufficient reaction, the concentration of the fluoride solution is 0.1-0.5 mol / L; S12: Rinse the nickel oxide film with deionized water to remove unreacted fluoride, and the rinsing time is 1-5 minutes.
[0013] As a preferred technical solution of the present invention, the steps of preparing the nickel oxide hole transport layer film are: A nickel oxide film is deposited on the surface of the substrate by sputtering coating, and the sputtering conditions are: the flow ratio of oxygen and argon is 150:100, the current is 9-12A, and the working gas pressure is 0.1-1Pa.
[0014] The present invention also provides a method for preparing an organic solar cell, comprising the following steps: Substrate preparation: Clean the glass substrate containing ITO to ensure that the surface is dust-free and dirt-free; Formation of the hole transport layer: depositing a nickel oxide film by direct current magnetron sputtering technology to obtain a hole transport layer, and then post-treating the nickel oxide film according to S1-S5; Preparation of the active layer: Add methylammonium iodide to an organic solvent, then add lead iodide and stir evenly, filter and then spin-coat on the post-treated hole transport layer to obtain the active layer; Preparation of electron transport layer: PCBM was first dispersed in chlorobenzene solution, spin-coated on the active layer, and then annealed; Silver electrode evaporation: Silver is evaporated under vacuum conditions as an electrode.
[0015] As a preferred technical solution of the present invention, the spin coating speed in the preparation of the active layer is 1000-3000 rpm, and the spin coating time is 30-60 s; The spin coating speed in the preparation of the electron transport layer is 2000-4000 rpm, and the spin coating time is 30-60 s.
[0016] The present invention also provides an organic solar cell, which is manufactured using the above-mentioned method for preparing the organic solar cell.
[0017] The beneficial effects of the present invention are: 1. The nickel oxide produced by direct current magnetron sputtering of the present invention is treated with a sodium hydroxide solution to treat the interface contact between the nickel oxide and the perovskite layer, thereby improving the conductivity of the nickel oxide film, improving the carrier concentration of the nickel oxide film, improving the energy band matching between the nickel oxide film and the organic light absorbing layer, reducing the interface defect density of the nickel oxide film, and enhancing the ability of the nickel oxide film to extract carriers from the organic light absorbing layer.
[0018] 2. By covering the hole transport layer with an aqueous solution of sodium hydroxide and performing annealing treatment, an effective passivation layer can be formed to solve the problem of disordered arrangement of ionic liquids at the interface and improve the performance and stability of perovskite devices.
[0019] 3. Sputtered NiO x The film contains a large amount of high-valent Ni and reactive groups that are harmful to perovskite. The transmittance of the film after interface treatment is significantly improved, the charge mobility of nickel oxide is improved, the interface non-radiative recombination is effectively suppressed, and an interface with low defect density is obtained, thereby effectively improving the open circuit voltage and photoelectric conversion efficiency of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 The present invention is a process flow chart of the method for treating the hole transport layer of an organic solar cell.
[0021] Figure 2 This is a comparison diagram of the test of the nickel oxide hole transport layer film post-treatment method IV of the present invention.
[0022] Figure 3 This is a process flow chart of the method for processing the hole transport layer of an organic solar cell according to Example 2.
[0023] Figure 4 Example 3 Process flow chart of a method for treating a hole transport layer of an organic solar cell.
[0024] Figure 5 The process flow chart of the method for preparing an organic solar cell of the present invention is shown in FIG. DETAILED DESCRIPTION
[0025] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] Embodiment 1 like Figure 1 As shown, a method for processing a hole transport layer of an organic solar cell comprises the following steps: S1: preparing a nickel oxide hole transport layer film and washing the nickel oxide film with deionized water.
[0027] S2: preparing a liquid to be adjusted and measuring an initial pH value of the liquid to be adjusted; In order to effectively prepare the nickel oxide hole transport layer film, the liquid to be adjusted can be selected from some suitable solutions, such as: deionized water, sodium hydroxide solution and organic solvent solution; Sodium hydroxide solution: What concentration of sodium hydroxide is dissolved in water? It can be adjusted to the expected pH range in advance and can be directly used as the solution to be adjusted. After adjusting the pH, the auxiliary material can be adsorbed; Organic solvent solutions: such as ethanol, acetone, etc. These solvents can provide different chemical environments, but attention should be paid to pH adjustment and compatibility with subsequent treatments; The liquid to be adjusted in the present invention is preferably deionized water, because it can provide a stable matrix for the subsequent addition of sodium hydroxide. At the same time, after introducing other components (such as fluorides or salts), fluoride solutions or acidic salt solutions can be flexibly selected to obtain a suitable reaction environment. In general, the key to the selection of the liquid to be adjusted is to ensure that there is no negative interference with the performance of the nickel oxide film during the treatment process.
[0028] S3: Calculate the required volume of sodium hydroxide aqueous solution, and add an appropriate amount of sodium hydroxide aqueous solution to the liquid to be adjusted in step S2 to adjust the pH of the solution to a suitable range. After the preparation is completed, the pH of the solution is 9-10. Preferably, the pH of the solution after the preparation is completed is 9.5; This stage aims to adjust the pH value of the liquid to the target value of 9.5 by adding sodium hydroxide solution to the liquid to be adjusted. In order to achieve precise control, this process includes necessary calculations, drop-by-drop addition and real-time monitoring; Use the following formula to calculate the required NaOH concentration and volume: C1V1=C2V2 Where C1 is the concentration of the NaOH solution to be added, V1 is the volume of the NaOH solution to be added (to be calculated), C2 is the final concentration after the reaction (depending on the total amount of the liquid to be adjusted and the expected pH, usually requiring experimental correction), and V2 is the total volume of the liquid to be adjusted (for example, if there is 100 mL of the liquid to be adjusted, then V2 = 100 mL). The concentration of the NaOH solution is 0.1-0.5 mol / L.
[0029] S4: evenly spread the solution in step S3 on the surface of the cleaned nickel oxide hole transport layer film, and soak for 1-15 minutes to ensure sufficient reaction; When cleaning the nickel film, the nickel film can be rinsed under flowing deionized water to ensure that surface contaminants are removed; The prepared sodium hydroxide solution is evenly coated on the surface of the nickel film, and then preferably immersed in it for 5 minutes. The purpose of this step is to ensure that NaOH is fully in contact with the nickel surface to achieve effective chemical reaction or surface treatment.
[0030] S5: rinse the nickel oxide hole transport layer film with deionized water to remove excess sodium hydroxide aqueous solution, and then dry the rinsed film to complete the treatment; In step S5, the deionized water is used for rinsing for 1-5 minutes, and the rinsed film is placed in an oven for drying at a temperature of 40°C-70°C for a drying time of 10-30 minutes; In the process of drying nickel film, the choice of temperature and duration has an important influence on the quality and performance of the film. The following are some optional drying temperature and duration ranges suitable for the treatment of nickel oxide hole transport layer film: Low temperature drying: 40℃ to 50℃, duration: 15 to 30min, suitable for drying heat-sensitive materials to reduce stress and deformation; Medium temperature drying: 50℃ to 70℃, duration: 20 to 40min, suitable for commonly used standard drying conditions, suitable for drying most films to promote water evaporation while maintaining the stability of the film structure.
[0031] High temperature drying: 70℃ to 100℃, duration: 10 to 20min, suitable for situations where faster drying is required, but care should be taken to avoid overheating and potential thermal damage to the film. For some materials, excessively high temperatures may cause phase change or film peeling; Preferably, the present invention recommends drying at 50° C. for 20 min.
[0032] Among them, in order to overcome the disordered arrangement of the interface between the direct current magnetron sputtered nickel oxide and the perovskite light absorbing layer and the defects at the interface between the nickel oxide and the perovskite, the present invention provides a method for treating the hole transport layer of a perovskite solar cell, wherein the interface contact between the nickel oxide and the perovskite layer is treated by a sodium hydroxide solution, the conductivity of the nickel oxide film is improved, the carrier concentration of the nickel oxide film is improved, the energy band matching between the nickel oxide film and the organic light absorbing layer is improved, the interface defect density of the nickel oxide film is reduced, and the ability of the nickel oxide film to extract carriers from the organic light absorbing layer is enhanced; by covering the hole transport layer with a sodium hydroxide aqueous solution and performing an annealing treatment, an effective passivation layer can be formed, the problem of disordered arrangement of the ionic liquid at the interface is solved, and the performance and stability of the perovskite device are improved.
[0033] It should be noted that both step S4 and step S5 are performed under air or inert gas (such as nitrogen) to prevent contamination.
[0034] Further, the step of preparing the nickel oxide hole transport layer film is: A nickel oxide film is deposited on the surface of the substrate by sputtering. The sputtering conditions are: the flow ratio of oxygen and argon is 150:100, the current is 9-12A, the working pressure is 0.1-1pa, and a high-purity (99.99%) nickel target is selected to ensure that the NiO generated during the sputtering process is x The quality of nanofilm.
[0035] Among them, DC magnetron sputtering nickel oxide deposits target atoms or ions onto a substrate to form a thin film by ionizing gas and sputtering the target. In the magnetron sputtering nickel oxide process, nickel metal is usually used as a target, and gas ions are formed by inert gases such as argon. A magnetic field is applied to aggregate and accelerate the ions, and finally deposit them onto the substrate. The magnetron sputtering nickel oxide process is an important method for preparing nickel oxide thin films. This process has the advantages of fast preparation speed, dense and uniform films, and strong controllability. By adjusting the process parameters and the properties of the target material, nickel oxide films with different thicknesses, structures and properties can be prepared to meet the needs of different application fields.
[0036] Specifically, when the flow ratio of oxygen to argon gas is set to 150:100, the concentration of oxygen is ensured to promote the oxidation of nickel to form NiO. x For thin films, the current is set to 9-12A to ensure sufficient bombardment effect and generate enough nickel ions for deposition. In order to effectively carry out DC magnetron sputtering, the recommended working vacuum pressure range is 0.1Pa to 1Pa. Further, the working vacuum pressure range is the low pressure range (0.2Pa-0.5Pa). Within this range, the quality and uniformity of the film are good, which is suitable for the deposition of oxide thin films, which helps to reduce the collision effect of gas molecules on sputtered particles. Preferably, the working vacuum pressure range is 0.36Pa.
[0037] It should be noted that during actual deposition, it is recommended to monitor the performance indicators such as film thickness and resistance during the sputtering process in order to further optimize the following conditions: Efficiency of vacuum pump: Ensure that the performance of the pump can be maintained within the recommended vacuum pressure range; Gas flow control: real-time adjustment of oxygen and argon gas flow rates and subsequent film analysis to confirm the optimal ratio.
[0038] like Figure 2 As shown, it can be clearly seen that after using the treatment method of the hole transport layer of the perovskite solar cell provided by the present invention, the conductivity of the nickel oxide film can be significantly improved.
[0039] Embodiment 2 like Figure 3 As shown, a method for processing a hole transport layer of an organic solar cell comprises the following steps: S1: preparing a nickel oxide hole transport layer film and washing the nickel oxide film with deionized water; S2: preparing a liquid to be adjusted and measuring an initial pH value of the liquid to be adjusted; S3: Calculate the required volume of sodium hydroxide aqueous solution, and add an appropriate amount of sodium hydroxide aqueous solution to the liquid to be adjusted in step S2 to adjust the pH of the solution to an appropriate range; S4: evenly spread the solution in step S3 on the surface of the cleaned nickel oxide hole transport layer film, and soak for 1-15 minutes to ensure sufficient reaction; S5: rinse the nickel oxide hole transport layer film with deionized water to remove excess sodium hydroxide aqueous solution, and then dry the rinsed film to complete the treatment; S6: Immerse the post-treated nickel oxide film in a fluoride solution and perform fluorination treatment for 1-15 minutes to ensure sufficient reaction. The concentration of the fluoride solution is 0.1-0.5 mol / L. Preferably, the immersion treatment time is 5 minutes to ensure that the film layer is fully in contact with the fluoride solution. The concentration of the fluoride solution is 0.1 mol / L.
[0040] Embodiment 3 like Figure 4 As shown, a method for processing a hole transport layer of an organic solar cell comprises the following steps: S1: preparing a nickel oxide hole transport layer film and washing the nickel oxide film with deionized water; S11: directly coating the cleaned nickel oxide film with a fluoride solution, soaking for 1-15 minutes to ensure sufficient reaction, the concentration of the fluoride solution is 0.1-0.5 mol / L, preferably, the soaking treatment time is 5 minutes, ensuring that the film layer is fully in contact with the fluoride solution, the concentration of the fluoride solution is 0.1 mol / L; S12: using deionized water to rinse the nickel oxide film to remove unreacted fluoride, the rinsing time is 1-5 minutes, preferably, the rinsing time is 3 minutes; S2: preparing a liquid to be adjusted and measuring an initial pH value of the liquid to be adjusted; S3: Calculate the required volume of sodium hydroxide aqueous solution, and add an appropriate amount of sodium hydroxide aqueous solution to the liquid to be adjusted in step S2 to adjust the pH of the solution to an appropriate range; S4: evenly spread the solution in step S3 on the surface of the cleaned nickel oxide hole transport layer film, and soak for 1-15 minutes to ensure sufficient reaction; S5: Rinse the nickel oxide hole transport layer film with deionized water to remove excess sodium hydroxide aqueous solution, and then dry the rinsed film to complete the post-processing.
[0041] Embodiment 2 and embodiment 3 respectively provide a process of adding fluorination treatment to the nickel film on the basis of embodiment 1.
[0042] Only the passivation layer using NaOH treatment solution: NaOH treatment solution can remove surface dirt and impurities by reacting with nickel oxide film and trigger surface chemical reaction. It can promote the dissolution of nickel ions to form a passivated nickel hydroxide (Ni(OH)2) layer, enhance the chemical stability of the film layer, and the formed nickel hydroxide layer can provide initial passivation to prevent further corrosion. However, the passivation layer is relatively thin, not uniform, and has weak effect, and its protection ability against certain corrosive environments is insufficient; First apply the fluoride solution and then apply the passivation layer of NaOH treatment solution: Fluoride (such as potassium fluoride or sodium fluoride) can form a fluoride layer of nickel fluoride (NiF2) or other fluorides on the nickel substrate. This layer can provide effective physical protection. The formation of nickel fluoride will affect the subsequent NaOH treatment and enhance the chemical corrosion resistance of the film layer. NaOH can also further improve the surface state on this basis, and may promote the uniform distribution of fluorine elements, increase the thickness and density of the layer. This composite treatment can form a thicker and more complex passivation layer, thereby improving corrosion resistance. The fluoride layer can seal the surface microstructure of the nickel oxide film to prevent the infiltration of moisture and corrosive substances. At the same time, the presence of fluorine elements can enhance the chemical stability of the film layer and increase its service life in harsh environments.
[0043] From the above comparison, it can be seen that using fluoride solution first and then NaOH treatment solution can form a more complex and more effective passivation layer as a whole. This layer not only provides physical protection, but also improves chemical stability by increasing the introduction of fluorine elements, thereby improving corrosion resistance.
[0044] The difference between Example 2 and Example 3 is that in Example 2, sodium hydroxide is added first and then the fluoride solution is added, while in Example 3, the fluoride solution is added first and then the sodium hydroxide is added.
[0045] Comparing the performance of the nickel oxide hole transport layer film obtained by the above two treatment methods (adding sodium hydroxide first and then adding fluoride solution, and adding fluoride solution first and then adding sodium hydroxide solution), the following performance parameters can be used as reference: Performance parameters Treatment method 1 (NaOH first) Treatment method 2 (fluoride first) Film thickness (nm) 50-100 60-120 Light transmittance(%) 85-90 75-85 Conductivity( / ) 0.05-0.15 0.03-0.1 <![CDATA[Carrier concentration (10 20 cm −3 ).]]> 1.0-2.0 0.8-1.5 Contact angle (°) 60-70 50-60 Stress (MPa) 30 20 Table 1 Comparison of properties of nickel oxide films obtained by two treatment methods Among them, the film thickness of treatment method 1 (NaOH first) is 50-100nm. The reasonable thickness ensures the electrical properties and light transmittance, but a thinner film may affect the mechanical properties of the film. The film thickness of treatment method 2 (fluoride first) ranges from 60-120nm. Thicker films may provide better strength and corrosion resistance. Treatment method 1 has a higher transmittance (85-90%), which is suitable for optoelectronic applications, indicating that the optical properties of the film are superior. Treatment method 2 has a lower transmittance (75-85%), which may reduce its performance in some optoelectronic device applications. Treatment method 1 has a higher conductivity range (0.05-0.15S / m), showing better conductivity and facilitating charge transport, while treatment method 2 has a relatively lower conductivity (0.03-0.1S / m), which may result in slightly poorer performance in electrical devices; Treatment method 1 has a higher carrier concentration (1.0-2.0), which helps to improve the effective transfer of charges, while treatment method 2 has a relatively low carrier concentration (0.8-1.5), which may affect the conductivity of the membrane; The contact angle of treatment method 1 was 60-70°, showing moderate hydrophobicity, which is suitable for some applications. The contact angle of treatment method 2 was smaller, 50-60°, showing higher hydrophilicity, which may affect the water wetting and cleaning ability of the membrane; Negative stress exists in both treatment methods 1 and 2, but the stress range of treatment method 1 is wider, which may have a positive effect on the adhesion and stability of the film; In addition, in terms of chemical stability, film density, and UV resistance, the film obtained by treatment method 2 is superior to the film obtained by treatment method 1.
[0046] In summary, treatment method 1 (NaOH first) performs better in electrical properties and transmittance, and is suitable for the application of optoelectronic devices, while treatment method 2 (fluoride first) has advantages in chemical stability and other aspects, and is more suitable for applications in harsh environments. For specific application requirements, the most appropriate treatment method can be selected according to various performance parameters.
[0047] In the present invention, the thin film obtained by treatment method 1 (NaOH first) is preferably used, which is more conducive to the use of solar cells.
[0048] Embodiment 4 Further, if Figure 5 As shown, a method for preparing an organic solar cell comprises the following steps: Substrate preparation: Clean the glass substrate containing ITO to ensure that the surface is dust-free and dirt-free. The material is ITO (indium tin oxide). ITO-coated glass substrates are widely used in perovskite solar cells due to their excellent transparent conductive properties. The cleaning process is as follows: First, the glass substrate is preliminarily cleaned using deionized water and a cleaning agent (such as an ultrasonic cleaning solution) to remove dust and oil on the surface; Secondly, further soak and wipe with acetone or ethanol to ensure the removal of inorganic chemical residues; After cleaning, use nitrogen spray to dry to avoid moisture residue; Before coating, after a deionized water wash, O2 plasma cleaning can be used to improve surface properties and increase interface contact with subsequent materials.
[0049] Formation of the hole transport layer: a nickel oxide film is deposited by direct current magnetron sputtering technology to obtain a hole transport layer, and then the nickel oxide film is post-processed according to S1-S5.
[0050] Preparation of the active layer: Add methylammonium iodide to an organic solvent, then add lead iodide and stir evenly, filter and then spin-coat on the post-treated hole transport layer to obtain the active layer; In the preparation process of the active layer, the characteristics and formation of perovskite materials play a key role in the performance of solar cells and other optoelectronic devices. Perovskite materials are usually composed of organic salts (such as MAI) and inorganic halides (such as PbI2). Through appropriate dissolution and deposition processes, perovskite films with excellent optoelectronic properties are finally generated. Its chemical formula is MAPbI 3; The molar ratio of MAI to PbI2 was set to 1:1, a ratio that is critical to ensure the formation of stoichiometric perovskite materials; Selection of organic solvents. DMSO or DMF are commonly used organic solvents that can effectively dissolve MAI and PbI2 and form a uniform precursor solution at high concentrations, ensuring that MAI and PbI2 are completely dissolved, which helps to form a uniform and dense perovskite structure in the subsequent spin coating process. After mixing and stirring, a 0.45µm microporous filter was used for preliminary filtration. This process was used to remove larger particulate matter to ensure that the prepared solution was uniform and particle-free to avoid affecting the subsequent spin coating process.
[0051] Preparation of electron transport layer: PCBM is first dispersed in chlorobenzene solution, spin-coated on the active layer, and then annealed. Through heat treatment, the aggregation state of PCBM can be improved, the electron transport performance can be enhanced, and the defect density can be reduced; The weight concentration of PCBM is controlled at 20-30 mg / ml. It must be ensured that it is fully dissolved in chlorobenzene. The stirring time should be more than 60 minutes to promote the full dispersion of PCBM. During the annealing process, a nitrogen protective atmosphere is introduced to prevent the film from being oxidized at high temperature. The annealing temperature and time will affect the aggregation state of PCBM. Usually, thermal annealing is performed at 120°C for 30 minutes. After annealing, the sample is allowed to cool naturally to room temperature to avoid film cracks caused by sudden cooling.
[0052] Silver electrode evaporation: Silver is evaporated under vacuum conditions as an electrode. The evaporation of silver electrodes is one of the key steps in preparing high-efficiency optoelectronic devices. Preferably, the thickness of the silver electrode film is 100 nm. In the preparation process of active layer and electron transport layer, spin coating speed and spin coating time are also important parameters, which directly affect the uniformity and thickness of the layer. For this reason: In the preparation of the active layer, the spin coating speed is 1000-3000rpm, and the spin coating time is 30-60s (this time period can ensure the formation of a perovskite film of appropriate thickness (about 100-300nm)) to ensure that the film thickness is between 100-300nm. After spin coating, it needs to be cooled to room temperature to reduce internal stress and avoid the formation of cracks, and heat treatment (about 100°C, 10-30min) is performed to promote the crystallization of perovskite. The spin coating speed is selected according to the required film thickness. Higher spin coating speeds usually form thinner films, while lower speeds help to form thicker films. The spin coating speed in the preparation of the electron transport layer is 2000-4000 rpm, and the spin coating time is 30-60 s.
[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for processing a hole transport layer of an organic solar cell, characterized in that: The following steps are involved: S1: preparing a nickel oxide hole transport layer film and washing the nickel oxide film with deionized water; S2: preparing a liquid to be adjusted and measuring an initial pH value of the liquid to be adjusted; S3: Calculate the required volume of sodium hydroxide aqueous solution, and add an appropriate amount of sodium hydroxide aqueous solution to the liquid to be adjusted in step S2 to adjust the pH of the solution to an appropriate range; S4: evenly spread the solution in step S3 on the surface of the cleaned nickel oxide hole transport layer film, and soak for 1-15 minutes to ensure sufficient reaction; S5: Rinse the nickel oxide hole transport layer film with deionized water to remove excess sodium hydroxide aqueous solution, and then dry the rinsed film to complete the post-processing.
2. The method for processing a hole transport layer of an organic solar cell according to claim 1, characterized in that: The pH of the solution in step S3 is 9-10.
3. The method for processing a hole transport layer of an organic solar cell according to claim 1, characterized in that: The deionized water rinsing time in step S5 is 1-5 minutes; The washed film is placed in an oven for drying at a temperature of 40°C-70°C and a drying time of 10-30 minutes.
4. The method for processing a hole transport layer of an organic solar cell according to claim 1, characterized in that: Step S4 and step S5 are both performed under air or inert gas.
5. The method for processing a hole transport layer of an organic solar cell according to any one of claims 1 to 4, characterized in that: The following steps are also included: S6: soaking the post-treated nickel oxide film in a fluoride solution and performing fluorination treatment, soaking for 1-15 minutes to ensure sufficient reaction, and the concentration of the fluoride solution is 0.1-0.5 mol / L.
6. The method for processing a hole transport layer of an organic solar cell according to any one of claims 1 to 4, characterized in that: The steps between step S1 and step S2 also include the following steps: S11: directly coating the cleaned nickel oxide film with a fluoride solution, soaking for 1-15 minutes to ensure sufficient reaction, the concentration of the fluoride solution is 0.1-0.5 mol / L; S12: Rinse the nickel oxide film with deionized water to remove unreacted fluoride, and the rinsing time is 1-5 minutes.
7. The method for processing a hole transport layer of an organic solar cell according to claim 1, characterized in that: The steps of preparing the nickel oxide hole transport layer film are: A nickel oxide film is deposited on the surface of the substrate by sputtering coating, and the sputtering conditions are: the flow ratio of oxygen and argon is 150:100, the current is 9-12A, and the working gas pressure is 0.1-1Pa.
8. A method for preparing an organic solar cell, comprising the method for treating a hole transport layer of an organic solar cell according to any one of claims 1 to 7, characterized in that: The following steps are involved: Substrate preparation: Clean the glass substrate containing ITO to ensure that the surface is dust-free and dirt-free; Formation of the hole transport layer: depositing a nickel oxide film by direct current magnetron sputtering technology to obtain a hole transport layer, and then post-treating the nickel oxide film according to S1-S5; Preparation of the active layer: Add methylammonium iodide to an organic solvent, then add lead iodide and stir evenly, filter and then spin-coat on the post-treated hole transport layer to obtain the active layer; Preparation of electron transport layer: PCBM was first dispersed in chlorobenzene solution, spin-coated on the active layer, and then annealed; Silver electrode evaporation: Silver is evaporated under vacuum conditions as an electrode.
9. The method for preparing an organic solar cell according to claim 8, characterized in that: In the preparation of the active layer, the spin coating speed is 1000-3000 rpm and the spin coating time is 30-60 s; The spin coating speed in the preparation of the electron transport layer is 2000-4000 rpm, and the spin coating time is 30-60 s.
10. An organic solar cell, manufactured using the method for preparing an organic solar cell according to any one of claims 8 to 9.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN107565023A
Inorganic hole transport material for solar cell and preparation method and application thereof
CN112186108A
Solar cell based on energy level adjustable nickel oxide hole transport layer and preparation method
CN113903860A
Nickel oxide hole transport layer, perovskite solar cell and preparation method
CN118540961A
Cited By
NiOx-HTL cleaning method based on oxygen-alkali micron bubble system
CN121017163A